Mejores Prácticas de Manejo en el Area Agrícola de los Everglades: Control de la Aplicación de Fertilizantes - Timothy A. Lang; Samira H. Daroub; Orlando A. Diaz; Viviana M. Nadal; Ming Chen (EDIS, 2007)
SL-232-Sp, a 5-page illustrated fact sheet by T.A. Lang, S.H. Daroub, O.A. Diaz, V.M. Nadal, and M. Chen, is the Spanish language version of SL-232, "Best Management Practices in the Everglades Agricultural Area: Fertilizer Application Control." It provides current implementation guidelines for this BMP designed to reduce drainage P loads in the Everglades Agricultural Area (EAA) by controlling the timing and placement of fertilizer applications. Includes references. Published by the UF Department of Soil and Water Sciences, May 2007.